Management of Dens Invaginatus in a Maxillar Lateral Incisor with Open Apex and Persistent Sinus Tract: a Case Report - Küçükekenci Funda Fundaoğlu (Balkan Journal of Dental Medicine, 2018)
Background/Aim: Dens invaginatus is a developmental anomaly of teeth. The endodontic treatment of these teeth may be difficult because of adversity in accessing the root canals and also complicated variations of internal structure. In this case, the report is presented the nonsurgical management and follow-up of a tooth with class II dens invaginatus with an open apex and sinus tract.